Assessment of performance and livelihood generated through community based goat production in Bangladesh - Faruque, MO; Choudhury, MP; Ritchil, CH; Tabassum, F; Hashem, MA; Bhuiyan, AKFH (SAARC Journal of Agriculture, 2017)
The study was undertaken to investigate the performance of Black Bengal goats and livelihood generated through goat rearing at 3 different villages namely Kaichapur, Salia and Shimulia at Phulpur Upazila (GPS: 24.9500°N and 90.3500°E) of Mymensingh district in Bangladesh. The average birth weight, body weight at 6 and 12 months of Black Bengal goat (BBG) were 1.03 ± 0.01 kg, 7.75 ± 0.09 and 12.77 ± 0.16 kg, respectively and daily body weight gain at 0-6 and 6-12 months of age were 34.38±0.54 and 24.62±0.57 g respectively. The average litter size of does was 1.51±0.05 and kid mortality rate was 12.58%. The study revealed that, most of the goat owners were housewives. The educational status and goat rearing system of the farmers were also observed. Most of the farmers were either Primary (55%) or illiterate (38.3%). About 3.33% were below Secondary School certificate and 1.67% Higher Secondary School certificate level. Few farmers have completed their graduation (1.67%). The average net profit from one goat in a year was Tk.754. The expenditure on food purchase, health care, education, clothing, housing condition and social status of the farmers were increased, respectively at a scale of 22.79%, 6.56%, 14.47%, 4.34%, 14.22% and 19.35% due to increase of their income from goat rearing. SAARC J. Agri., 14(2): 12-19 (2016)